1995
DOI: 10.1146/annurev.ph.57.030195.000245
|View full text |Cite
|
Sign up to set email alerts
|

Amarcord

Abstract: Unfortunately, one has to choose between describing science, and doing it.John Maynard Smith YEARS OF LEARNINGI was born 1924 in Bern. My father was a physician who had obtained his training before the First World War. He believed in the power of rational thinking and in his spare time entertained my younger brother and myself with various scientific tricks. He showed us, by letting rise to the ceiling the ashes of burning tissue paper, that air becomes lighter upon heating; we learned about catalysis by setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Frustrated by the failure to observe the expected stimulation of Na + transport, Schatzmann decided to try another steroid, k-strophanthoside, which produced a clear inhibition of the pump. An account of this discovery is provided in Schatzmann's recollection published in 1995 (Schatzmann, 1995). It quickly became apparent that rodent Na,K-ATPase is far less sensitive to inhibition by cardiac glycosides than other species.…”
Section: Session IV Inherited Dysfunction Of Cation Pumps (Carolyn Slayman Yale University)mentioning
confidence: 99%
“…Frustrated by the failure to observe the expected stimulation of Na + transport, Schatzmann decided to try another steroid, k-strophanthoside, which produced a clear inhibition of the pump. An account of this discovery is provided in Schatzmann's recollection published in 1995 (Schatzmann, 1995). It quickly became apparent that rodent Na,K-ATPase is far less sensitive to inhibition by cardiac glycosides than other species.…”
Section: Session IV Inherited Dysfunction Of Cation Pumps (Carolyn Slayman Yale University)mentioning
confidence: 99%
“…Hans Jürg Schatzmann died on 2 October 2021, at the age of 97. An autobiographical account with details of his life and career was published in Annual Reviews of Physiology in 1995 after he retired from the University of Bern, Bern, Switzerland [1]. Figure 1 is republished from that article.…”
mentioning
confidence: 99%
“…In late 1965, Privat Dozent (more-or-less equivalent to an assistant or associate professor) Schatzmann became the Professor of Veterinary Pharmacology. We Reproduced, with permission conveyed through Copyright Clearance Center, Inc., from [1].…”
mentioning
confidence: 99%
“…A hypothesis suggested that mineralocorticoids (MC) might be involved in the regulation of membrane transports. Schatzmann reported in his very readable autobiographical essay (Schatzmann 1995) that he, initially, was not aware that the stereochemistry of cardiac glycosides differs greatly from the one of cholesterol-derived steroid hormones. Therefore, he expected some kind of competitive interaction between MC and ouabain and was surprised that its inhibitory action was completely unaffected by MC.…”
mentioning
confidence: 99%